PERILAKU MAHASISWA PRODI PROFESI NERS TERHADAP VAKSINASI HEPATITIS B - Huriatul Masdar; Sitti Zuhairah; Rahmat Azhari Kemal; Fajri Marindra Siregar; Dedi Afandi (Fakultas Keperawatan, Universitas Riau, 2022)
Hepatitis B is a global health problem. Health workers are at high risk for hepatitis B infection. Among health workers, nursing students are at high risk for hepatitis B infection. One of the prevention efforts against hepatitis B infection is vaccination. Nursing students are the group that must be prioritized for vaccines. However, in Indonesia there is no mandatory policy for health workers to be vaccinated against hepatitis B, especially nursing students. The implementation of self-vaccination is determined by the behavior of nursing students. This study aimed to describe the knowledge, attitudes and actions of students of the Professional Nursing Study Program at the University of Riau towards hepatitis B vaccination. The study was conducted with a cross-sectional design. About 83 respondents were involved in this study, using a simple random sampling technique taken based on inclusion and exclusion criteria. The instrument used is a questionnaire that has been tested for validation and reliability. The results showed 53% respondents had a good knowledge, 63,9% had a positive attitude and 51,8% respondents had carried out hepatitis B vaccination. Statistical analysis using Kolmogorov-Smirnov test showed there were significant difference between knowledge and attitude (p=1,000) or knowledge and action (p=1,000). In can be concluded that there were no significant association between knowledge and attitude or knowledge and action toward hepatitis B vaccination among students of Nurse Study Program University of Riau.